Оптимальне проектування захисної оболонки атомної електростанції при імпульсному навантаженні - Сметанкіна, Наталя Володимирівна; Меркулова, Альона Ігорівна; Меркулов, Дмитро Олександрович; Місюра, Сергій Юрійович (Інститут прикладних проблем механіки і математики ім. Я. С. Підстригача НАН України, 2021)
А problem on the optimal design of a multilayer element of atomic power plants by a minimum mass criterion at impulse loading is formulated. As a method for the optimization, a modified version of the hybrid method of optimization with an adaptive control by computational process is used. Two optimal cover designs are obtained.
Optimal design of the protective cover of a nuclear power plant under impulse loading
Keywords: захисна оболонка; атомна електростанція; імпульсне навантаження; реакторні блоки; protective cover; nuclear power plant; impulse loading